Estimulación temprana y desarrollo lingüístico en niños sordos con implante coclear: el primer año de experiencia auditiva - Moreno-Torres, Ignacio; Cid, María del Mar; Santana, Rafael; Ramos, Ángel (Revista de Investigación en Logopedia, 2011)
The present study analyzes development in a group of 10 deaf children that have been fitted with a cochlear implant (CI) before their second birthday. The main aim of this study is to explore the extent to which post-implantation development is influenced by the degree of stimulation received by the children. Data were obtained about perception (parental questionnaire), and pre-linguistic and linguistic production (spontaneous speech samples and parental questionnaires). Also, a quantitative measure of the degree of stimulation of each child was obtained pre- and post- implantation. Results showed important intra-group variability: 1) in the rate of language development (expressive lexicon after 12 months of CI use); and 2) in the degree of stimulation. Statistic analysis confirmed that the degree of stimulation after 12 months of auditory experience is the only variable that correlates significantly with language development at that moment. The following variables did not correlate with expressive language: age at implantation, perception after three months of CI use, and babbling onset. Such results confirm the major role of early stimulation for the development of CI users, and especially the important role of the family in this process.